Evaluation of Dental Students' Knowledge and Attitudes About Early Childhood Caries - İPEK, İrem; TUNCER, Kevser (Selcuk University, 2024)
Background: Early childhood caries (ECC) causes serious and widespread oral health problems in children. This study aimed to evaluate the knowledge, attitudes and clinical practices of undergraduate dental students about ECC. Method: The study included 4thand 5thyear dental intern students who were treating patients. A 16-question survey form was prepared using the literature and the questionnaire prepared with the online survey program was sent via Google Forms. Distributions were compared using Pearson Chi square test. A significant difference was defined as 0.05. Results: When the awareness and knowledge levels about ECC were examined, 4th grade students had lower knowledge levels than 5th grade students. 5th grade students reported that they examined and diagnosed a higher rate of ECC cases. Conclusion: It is important to make clinical trainings more comprehensive and systematic for the prevention and treatment of ECC. © 2024, Selcuk University. All rights reserved.
Diş Hekimliği Öğrencilerinin Erken Çocukluk Çağı Çürükleri Hakkında Bilgi ve Tutumlarının Değerlendirilmesi
Keywords: Dental students; Early childhood caries; Education; Oral health